2013
DOI: 10.1016/j.psep.2012.05.008
|View full text |Cite
|
Sign up to set email alerts
|

Thermal instability and runaway criteria: The dangers of disregarding dynamics

Abstract: Two exemplary exothermic processes, synthesis of nitroglycerine in a continuous stirred tank reactor (CSTR) and synthesis of the explosive RDX in a CSTR, are used to demonstrate the dangers of ignoring the system dynamics when defining criteria for thermal criticality or runaway. Stability analyses are necessary to prescribe such criteria, and for these systems prove the presence of dangerous oscillatory thermal instability which cannot be detected using the steady state thermal balances.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
14
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 30 publications
0
14
0
1
Order By: Relevance
“…In the application of FDI, many authors have confined their works to a simplified model in which the chemical reaction is not included (see References [15,16,[19][20][21][22]). However, there are many parameters which should be taken into consideration when a chemical reaction is introduced.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the application of FDI, many authors have confined their works to a simplified model in which the chemical reaction is not included (see References [15,16,[19][20][21][22]). However, there are many parameters which should be taken into consideration when a chemical reaction is introduced.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, further research such as fault diagnosis and fault-tolerant control of this HEX reactor could be carried out based on this model. The modeling methodology specified in this paper is not restricted, and could also be used for other reactions and other sizes of HEX reactors.Processes 2019, 7, 454 2 of 20 essential to completely understand the dynamic characteristics of a new piece of equipment in terms of process safety [8,22] and further control. Like most cases, a cell-based model was used in this paper, i.e., each cell is modeled by means of energy and mass balances [23][24][25][26][27].…”
mentioning
confidence: 99%
“…Thus, the parametric sensitivity analysis allows identifying temperature maxima (hot spots) into the reactor and runaway criteria; while the dynamic one lets to track thermal stability, showing how the thermal behavior is changing under the variations of different operational parameters . It has already been demonstrated that dynamic analysis based on the singularity theory is a reliable tool to study exothermic reactive systems . It provides a useful framework for classifying branching phenomena in which different types of multiplicity of the nonlinear model can be found.…”
Section: Introductionmentioning
confidence: 99%
“…The main reasons are the nonlinear behaviour (Kvasnica et al, 2010), multiple steady states (Švandová et al, 2005), potential safety threats in reactors with exothermic chemical reactions (Ball and Gray, 2013) or presence of various uncertainties. Some of them arise from varying or not exactly known parameters, as e.g.…”
Section: Introductionmentioning
confidence: 99%